2017
DOI: 10.1002/2016gl071303
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of Ahuna Mons from Dawn mission's visible‐infrared spectrometer

Abstract: Ahuna Mons is the highest mountain on Ceres. A unique complex in terms of size, shape, and morphology, Ahuna is bordered by flanks of the talus around its summit. Recent work by Ruesch et al. () based on Dawn's Framing Camera images shed light on the possible origin of Ahuna Mons. According to Ruesch et al. (2016), Ahuna Mons is formed by a volcanic process involving the ascent of cryomagma and extrusion onto the surface followed by dome development and subsequent spreading. Here we analyzed in detail the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…The simplest explanation is that Ceres' crust is neither purely ice (the case studied in Bland, ) nor purely rock but an ice‐rock‐salt hydrate mixture that allows some relaxation at the longest wavelengths but is able to support the topography on the shorter wavelengths over geologic timescales. This suggested composition is supported by visible and infrared spectrometer (VIR) observations, which detected salts in the form of sodium carbonates and ammonium salts at Occator (De Sanctis et al, ), as well as sodium carbonates at Ahuna Mons (Zambon et al, ). Adding silicates or salts into water ice increases crustal density, implying that the crustal density must exceed a minimum value in order to meet the required mechanical strength.…”
Section: Discussionmentioning
confidence: 70%
“…The simplest explanation is that Ceres' crust is neither purely ice (the case studied in Bland, ) nor purely rock but an ice‐rock‐salt hydrate mixture that allows some relaxation at the longest wavelengths but is able to support the topography on the shorter wavelengths over geologic timescales. This suggested composition is supported by visible and infrared spectrometer (VIR) observations, which detected salts in the form of sodium carbonates and ammonium salts at Occator (De Sanctis et al, ), as well as sodium carbonates at Ahuna Mons (Zambon et al, ). Adding silicates or salts into water ice increases crustal density, implying that the crustal density must exceed a minimum value in order to meet the required mechanical strength.…”
Section: Discussionmentioning
confidence: 70%
“…; Zambon et al. ), such as Cerealia Facula in the middle of crater Occator, or enriched in organics similar to those discovered in the region of crater Ernutet (De Sanctis et al. ; Pieters et al.…”
Section: Tools and Techniquesmentioning
confidence: 96%
“…The northern flanks of Ahuna Mons, the highest mountain on Ceres, also display a larger amount of Ca‐carbonates and Na‐carbonates compared to surrounding regions (Zambon et al. ). Water‐ice–rich units mixed with low‐albedo components were discovered only in about 10 specific places at the surface, at latitudes poleward of 30° in fresh craters near rim shadows (Combe et al.…”
Section: Introductionmentioning
confidence: 99%
“…The steep ( ∼30-40 °) flanks of Ahuna Mons are composed of a bright (high albedo) material that has been proposed to consist of salts . Recently, Zambon et al (2017) concluded that the edifice exhibits high abundances of carbonates and low portions of hydrous minerals relative to the average surface composition of Ceres. The appearance and composition of Ahuna Mons make it Ceres' most unique landform and, along with Occator's bright spots, among the most interesting of Dawn's discoveries.…”
Section: Kmmentioning
confidence: 99%